2001
DOI: 10.1038/sj.bmt.1703184
|View full text |Cite
|
Sign up to set email alerts
|

Allogeneic peripheral blood stem cell transplantation (PBSCT) from HLA-identical sibling donors in children with hematological diseases: a single center pilot study

Abstract: Summary:Between February 1995 and July 1999 25 pediatric patients (8 months to 14 years old) underwent peripheral blood stem cell transplantation (PBSCT) from an HLA-identical sibling donor. Diagnoses included ALL (17), non-ALL (6), and non-malignant disease (2). GVHD prophylaxis consisted of cyclosporine plus methotrexate (15), only cyclosporine (8), cyclosporine plus prednisone (1), or nothing (1). All donors (6 months to 41 years old) received G-CSF at 10 g/kg/day subcutaneously for 4-5 days and on day 5 un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 55 publications
(66 reference statements)
0
6
0
Order By: Relevance
“…While some studies report a higher incidence of chronic GVHD with PBSC transplantation, 38-41 others do not indicate a difference in chronic GVHD. 42 Our results demonstrate that although the difference is not statistically significant, the use of allogeneic PBSCs rather than BMSCs may lead to better OS in recipients of matched sibling allografts for pediatric AML patients.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…While some studies report a higher incidence of chronic GVHD with PBSC transplantation, 38-41 others do not indicate a difference in chronic GVHD. 42 Our results demonstrate that although the difference is not statistically significant, the use of allogeneic PBSCs rather than BMSCs may lead to better OS in recipients of matched sibling allografts for pediatric AML patients.…”
Section: Discussionmentioning
confidence: 57%
“…36 Although several studies document more rapid hematopoietic recovery after PBSC transplantation in adult and pediatric patients, [37][38][39][40][41][42] there is still substantial controversy regarding acute and chronic GVHD, TRM, relapse, and survival. While some studies report a higher incidence of chronic GVHD with PBSC transplantation, 38-41 others do not indicate a difference in chronic GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Patients in this study had similar rates of aGVHD, but rates of cGVHD were higher with a relative risk of 1.85 in the PBSC group [17]. Thus, despite the lack of randomized studies in children it appears that he risk of cGVHD with PBSC is higher than BM, though it is unclear of the overall effects on TRM and relapse free survival [96,97]. …”
Section: Risk Factorsmentioning
confidence: 96%
“…According to the European Bone Marrow Transplantation (EBMT) data, it is estimated that about 500–600 children become donors of haematopoietic progenitor cells (HPC) for siblings undergoing allogeneic stem cell transplantation in Europe every year (Stycznski, personal communication). Although most institutions used bone marrow HPC, several studies have reported on the use of children as donors for peripheral blood progenitor cells (PBPC) (Kawano et al , 1999; Levine et al , 2000; Benito et al , 2001; González‐Vicent et al , 2002; Watanabe et al , 2002; Pérez et al , 2007). However, there is little information regarding donor safety and early side effects of PBPC collection, and variables predicting the yield.…”
mentioning
confidence: 99%